Combined Treatment of High-Flow Scalp Arteriovenous Malformations. Issue 3 (7th May 2022) - Janssen, Pierce L.; Taub, Peter J.; Marayati, Naoum Fares; Shigematsu, Tomoyoshi; Berenstein, Alejandro
Abstract : Introduction: Appropriate treatment of scalp arteriovenous malformations (SAVMs) remains largely unclear given the rarity of reported cases. This single-institution case series presents consecutive patients with extracranial SAVMs and long-term follow up. The primary aim of this study was to review treatment decisions, evaluate clinical outcomes, and compare our experience to available literature in order to better understand SAVMs and improve future outcomes. Materials and Methods: A retrospective review of consecutive patients with extracranial SAVMs between January 2015 and December 2019 was performed. Treatment factors of interest included embolization method, embolic agents, and decision to proceed with surgical resection. Relevant clinical outcomes included recurrence rates, cure rates, and complications. Results: Seven patients were included in the present series. Satisfactory outcomes were ultimately achieved for all 7 patients using embolization with or without combined surgical resection. Embolizations performed in combination with resection were curative in 4 of 4 cases (100%). Embolizations performed without resection were curative in 0 of 4 cases (0%), satisfactory in 2 of 4 cases (50%), and unsatisfactory in 2 of 4 cases (50%). Discussion: All SAVM patients in this series were treated satisfactorily using embolization with or without operative resection. This study strongly suggests that embolization combined with surgical resection during the same admission yields the best treatment outcomes for SAVMs, specifically demonstrating lower rates of recurrence and embolization-related complications. Decisions on whether or not to proceed with resection should be made by the interventional radiologist, the plastic surgeon, and the patient together.